2016
DOI: 10.1590/s0102-865020160050000008
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane preconditioning during myocardial ischemia-reperfusion reduces infarct size and preserves autonomic control of circulation in rats

Abstract: PURPOSE:To investigate the myocardial ischemia-reperfusion with sevoflurane anesthetic preconditioning (APC) would present beneficial effects on autonomic and cardiac function indexes after the acute phase of a myocardial ischemia-reperfusion. METHODS:Twenty Wistar rats were allocated in three groups: control (CON, n=10), myocardial infarction with sevoflurane (SEV, n=5) and infarcted without sevoflurane (INF, n=5). Myocardial ischemia (60 min) and reperfusion were performed by temporary coronary occlusion. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Hemodynamic measurements were not performed, but they exhibit good correlations with echocardiography parameters [ 12 ]. Of note, our left ventricular ejection fraction figures for ablated and sham animals are comparable to other reports concerning infarcted rats and controls [ [29] , [30] , [31] , [32] ]. Mild systolic ventricular dysfunction was consistently induced in our model.…”
Section: Discussionsupporting
confidence: 90%
“…Hemodynamic measurements were not performed, but they exhibit good correlations with echocardiography parameters [ 12 ]. Of note, our left ventricular ejection fraction figures for ablated and sham animals are comparable to other reports concerning infarcted rats and controls [ [29] , [30] , [31] , [32] ]. Mild systolic ventricular dysfunction was consistently induced in our model.…”
Section: Discussionsupporting
confidence: 90%
“…• Neuregulin-1 [134][135][136][137][138] • Ghrelin [139] • Vasopressin [140] • Anesthetic preconditioning [141] Non-pharmacological interventions…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Restora-tion of blood flow to an ischemic heart is necessary to salvage the ischemic myocardium, but reperfusion of an ischemic region can result in myocardial ischemia/reperfusion (IR) injury due to oxidative stress [2]. Studies have shown that sevoflurane postconditioning (SPostC) could protect the myocardium against reperfusion-induced injury and reduce myocardial infarct size [3,4]. However, patients with diabetes have a remarkably higher mortality rate owing to increased IR injury and the beneficial effects of SPostC almost completely disappeared [5][6][7].…”
Section: Introductionmentioning
confidence: 99%